Increased risk of inflammatory bowel disease in ankylosing spondylitis compared to psoriasis - He, Zhen; Zhang, Yi-Nan; Wei, James Cheng-Chung; Dai, Sheng-Ming (Frontiers in Immunology, 2026)
BackgroundWhile ankylosing spondylitis (AS) and psoriatic arthritis (PsA) share similar immune dysregulation, their relative risks for inflammatory bowel disease (IBD), including definitive subtypes (Crohn’s disease [CD] and ulcerative colitis [UC]) and possible subtypes (indeterminate colitis [IC] and microscopic colitis [MC]), remain unquantified. We aimed to establish comparative IBD risk gradients among AS, psoriasis (PSO), and PsA cohorts.MethodsThe study utilized a long-term retrospective cohort design by analyzing an electronic health record database. Propensity score matching (PSM) was used to adjust multiple confounders. Cox proportional hazards models and log rank test were employed to evaluate the risk of IBD development.ResultsThe study included 26,610 patients with AS and 322,317 with PSO (2005–2023). After PSM, 26,569 matched pairs were analyzed. Compared to PSO, AS was associated with a significantly higher risk of definite IBD [hazard ratio (HR) = 2.96, 95% CI: 2.64–3.33], CD (HR = 3.38, 95% CI: 2.90–3.94), UC (HR = 2.43, 95% CI: 2.07–2.85), and IC (HR = 2.45, 95% CI: 1.33–4.51), but not MC. Subgroup analyses confirmed a consistently higher IBD risk in AS across all ages, sexes, races, BMI categories, and comorbidity profiles. Compared to the general population, AS conferred the highest independent risk for definite IBD (HR = 4.22, 95% CI: 3.60–4.94), followed by PsA (HR = 1.52) and PSO (HR = 1.37). AS also showed a 2.60-fold higher definite IBD risk than PsA (95% CI: 2.32–2.92).ConclusionsAS is the phenotype most strongly associated with IBD among the studied spectrum. Compared to PSO, AS confers a significantly higher risk of CD, UC, and IC, and it carries a greater burden of definite IBD than PsA or the general population.